Incubation increases oxidative imbalance compared to chick rearing in a seabird, the Magellanic penguin (Spheniscus magellanicus) - Colominas Ciuró, Roger (2017)
It is expected that activities which require a high use of energy could generate higher oxidative stress. In the present study, we have compared two breeding periods (incubation and chick rearing) with different energetic demands in the Magellanic penguin, predicting a higher oxidative unbalance during chick rearing since involves higher demanding activities such as chick feeding and greater nest protection than during incubation. Specifically, we predicted higher oxidative damage and lower antioxidant defences during chick rearing than during incubation. Fieldwork was conducted in a Magellanic penguin colony located in Estancia San Lorenzo (42°05′S, 63°49′W), Peninsula Valdes, Argentina, during the breeding season of 2014–2015. Surprisingly, our results did not support our initial prediction. Incubating adults had their oxidative status unbalanced showing significantly lower antioxidant levels than those rearing chicks. Moreover, oxidative damage did not show any significant variation between both breeding periods. Further, we did not find differences in oxidative status between sexes. Our results suggest that incubation is a highly demanding activity compared to chick rearing in terms of oxidative balance since the lower presence of antioxidants can be explained as they have probably depleted to limit oxidative damage by ROS. Differential foraging effort could explain such results as Magellanic penguins adjust their foraging location to prey availability performing longer foraging trips during incubation than during chick rearing which increases the energy costs and therefore imbalance penguins oxidative status. Our results show the importance of examining physiological markers such as oxidative stress to assess differences during the breeding cycle and how the behaviour at sea could explain such differences in seabirds.